Vitamin D supplementation to prevent asthma exacerbations: a systematic review and meta-analysis of individual participant data. Issue 11 (November 2017) - Jolliffe, David A; Greenberg, Lauren; Hooper, Richard L; Griffiths, Christopher J; Camargo, Carlos A; Kerley, Conor P; Jensen, Megan E; Mauger, David; Stelmach, Iwona; Urashima, Mitsuyoshi; Martineau, Adrian R
Summary: Background: A previous aggregate data meta-analysis of randomised controlled trials showed that vitamin D supplementation reduces the rate of asthma exacerbations requiring treatment with systemic corticosteroids. Whether this effect is restricted to patients with low baseline vitamin D status is unknown. Methods: For this systematic review and one-step and two-step meta-analysis of individual participant data, we searched MEDLINE, Embase, the Cochrane Central Register of Controlled Trials, and Web of Science for double-blind, placebo-controlled, randomised controlled trials of vitamin D3 or vitamin D2 supplementation in people with asthma that reported incidence of asthma exacerbation, published between database inception and Oct 26, 2016. We analysed individual participant data requested from the principal investigator for each eligible trial, adjusting for age and sex, and clustering by study. The primary outcome was the incidence of asthma exacerbation requiring treatment with systemic corticosteroids. Mixed-effects regression models were used to obtain the pooled intervention effect with a 95% CI. Subgroup analyses were done to determine whether effects of vitamin D on risk of asthma exacerbation varied according to baseline 25-hydroxyvitamin D (25[OH]D) concentration, age, ethnic or racial origin, body-mass index, vitamin D dosing regimen, use of inhaled corticosteroids, or end-study 25(OH)D levels; post-hoc subgroup analyses were done according to sex and study duration. This study was registered with PROSPERO, number CRD42014013953. Findings: Our search identified 483 unique studies, eight of which were eligible randomised controlled trials (total 1078 participants). We sought individual participant data for each and obtained it for seven studies (955 participants). Vitamin D supplementation reduced the rate of asthma exacerbation requiring treatment with systemic corticosteroids among all participants (adjusted incidence rate ratio [aIRR] 0·74, 95% CI 0·56–0·97; p=0·03; 955 participants in seven studies; high-quality evidence). There were no significant differences between vitamin D and placebo in the proportion of participants with at least one exacerbation or time to first exacerbation. Subgroup analyses of the rate of asthma exacerbations treated with systemic corticosteroids revealed that protective effects were seen in participants with baseline 25(OH)D of less than 25 nmol/L (aIRR 0·33, 0·11–0·98; p=0·046; 92 participants in three studies; moderate-quality evidence) but not in participants with higher baseline 25(OH)D levels (aIRR 0·77, 0·58–1·03; p=0·08; 764 participants in six studies; moderate-quality evidence; pinteraction =0·25). p values for interaction for all other subgroup analyses were also higher than 0·05; therefore, we did not show that the effects of this intervention are stronger in any one subgroup than in another. Six studies were assessed as being at low risk of bias, and one was assessed as being at unclear risk of bias. The two-step meta-analysis did not reveal evidence of heterogeneity of effect ( I 2 =0·0, p=0·56). Interpretation: Vitamin D supplementation reduced the rate of asthma exacerbations requiring treatment with systemic corticosteroids overall. We did not find definitive evidence that effects of this intervention differed across subgroups of patients. Funding: Health Technology Assessment Program, National Institute for Health Research (reference number 13/03/25).